Development and characterization of soft bread cookie incorportaed with spent coffee grounds. - Basinang, Airesse Rae Prieto
Spent coffee ground (SCG) is a valuable by-product of coffee often discarded. It is seen with extensive potential as a functional food which led to the development of soft bread cookie incorporated with spent coffee grounds. Three varying ratios of 20:80 (F1), 25:75 (F2), and 30:70 (F3) percent weight per weight of spent coffee grounds and all-purpose flour, respectively were subjected to rank test for preference. F2 was the most preferred formulation (MPF) and was characterized for its physicochemical, proximate, and sensorial properties. Microbiological analysis was also conducted to SCG as raw material and soft bread cookie with SCG as finished product. The analyses of the soft bread cookie with SCG resulted to a pH value of 8.07 with 0.512aw with the proximate composition of the following: moisture content (5.83%), crude fat (21.93%), and ash content (1.54%), crude fiber (0.241%), crude protein (4.34%), and carbohydrate content (66.1%) of the soft bread cookie with SCG, SCG as a raw material had a microbial population of 4.4x105 CFU/g and positively identified with green-metallic sheen colonies. After exposure to heat, soft bread cookie with SCG had a reduced microbial population of 8.1x102 CFU/g and negatively for E. coli. The soft bread cookie with SCG was described to have a coffee brown color. The coffee aroma was very much distinguished while the coffee flavor was moderately tasted. The product has a potential in market sales with 40% of respondents agreed to it as yummy. Further analyses on spent coffee grounds and development of other food products are recommended.